Kecerdasan emosi dan kepuasan kerja dikalangan penjawat awam Perkhidmatan Awam Malaysia - Azlan Seruji,; Nurul-Azza Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to identify into the influence between emotional intelligence and achievement motivation towards job satisfaction among Public Service Psychology Officers. There are several research instruments that have been used to measure each of the variables in this study such as the Job Satisfaction Survey (JSS) created by Paul E. Spector (1985), Wong and Law Emotional Intelligence Scale (WLEIS) by Wong and Law (2002) and Cassidy and Lynn Achievement Motivation Scale (CLAMS) by Cassidy and Lynn (1989). Respondents of 196 Psychology and Assistant Psychology Officers from various backgrounds were involved in this study. The data obtained were analysed using Winsteps version 3.72.3 and Statistical Package For Social Science (SPSS) version 25 which involved internal consistency reliability analysis, descriptive statistical analysis and inferential statistical analysis. The findings of inferential analysis showed that there were no differences in job satisfaction, emotional intelligence and achievement motivation according to age, gender and duration of service while overall emotional intelligence has a significant relationship with job satisfaction. Analysis findings also found that the dimension of achievement motivation which is the work ethics has a significant relationships with job satisfaction. Meanwhile, emotional intelligence as a whole has a significant influence on job satisfaction. The dimension of emotional intelligence which is the self-emotional appraisal also have the significant influence towards job satisfaction. As for achievement motivation, only the dimension of work ethics do has a significant influence towards job satisfaction.